2013
DOI: 10.1093/jxb/ert266
|View full text |Cite
|
Sign up to set email alerts
|

Heritable variation and small RNAs in the progeny of chimeras of Brassica juncea and Brassica oleracea

Abstract: Chimeras have been used to study the transmission of genetic material and the resulting genetic variation. In this study, two chimeras, TCC and TTC (where the origin of the outer, middle, and inner cell layers, respectively, of the shoot apical meristem is designated by a ‘T’ for tuber mustard and ‘C’ for red cabbage), as well as their asexual and sexual progeny, were used to analyse the mechanism and the inheritance of the variation induced by grafting. Asexual TCC progeny were obtained by adventitious shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…The results indicated that there were a number of specific chemical-related genes in cell layer L1 (mainly controlled juice sacs) of OCJ were inherited from O, and others in L2 (mainly controlled peels) were inherited from C. This observation was consistent with the study that the juice sacs of a citrus periclinal chimera Ekuliku, obtained by grafting, were developed from L1 donor Nankan (C. unshiu), while the epicarp and mesocarp were both developed from L2&L3 donor Hamlin (C. sinensis) [19]. Moreover, our results also attested to the genetic regularity previously described in the leaf morphology variation of Brassica chimeras, that the variation was only controlled by the cells of the donor red cabbage and was reproducible and directional in progenies [20]. Furthermore, in the present study, we also found that the contents of the same chemical substances in different tissues of OCC were seperately apt to donor O or donor C.…”
Section: Metabolic Interrelationships Between Occ and Its Layer Sourcsupporting
confidence: 84%
See 1 more Smart Citation
“…The results indicated that there were a number of specific chemical-related genes in cell layer L1 (mainly controlled juice sacs) of OCJ were inherited from O, and others in L2 (mainly controlled peels) were inherited from C. This observation was consistent with the study that the juice sacs of a citrus periclinal chimera Ekuliku, obtained by grafting, were developed from L1 donor Nankan (C. unshiu), while the epicarp and mesocarp were both developed from L2&L3 donor Hamlin (C. sinensis) [19]. Moreover, our results also attested to the genetic regularity previously described in the leaf morphology variation of Brassica chimeras, that the variation was only controlled by the cells of the donor red cabbage and was reproducible and directional in progenies [20]. Furthermore, in the present study, we also found that the contents of the same chemical substances in different tissues of OCC were seperately apt to donor O or donor C.…”
Section: Metabolic Interrelationships Between Occ and Its Layer Sourcsupporting
confidence: 84%
“…While small RNAs expressions and DNA methylation have recently been considered to be involved in stock-scion to describe genetic variations in graft chimeras. For instance, researchers have found some conserved miRNAs were differentially expressed in graft chimera (Brassica juncea + B. oleracea) progeny rTTT (sexual self-crossing of the chimera) and donor plant TTT (B. juncea), which may contributed to the changes in expression of their target genes [20]. In this work, the content of some chemicals in OCC were between two donors but some were deviated far from both of donor parents.…”
Section: Speculation Of Genetic Laws In Chimeras' Metabolitesmentioning
confidence: 61%
“…Our previous study12 reported that heterogeneous small RNAs were transported from the red cabbage cells to the tuber mustard cells in chimera TTC, and apart from transmission, the expression of small RNAs changed significantly during the grafting stage, indicating that the communication and perturbation of heterogenous cells led to the fluctuation of variety and expression of small RNAs during grafting. That means the grafting is a complicated process which is involved in cell communication and stress.…”
Section: Discussionmentioning
confidence: 95%
“…donor Hamlin (C. sinensis) [3]. Similarly, the leaf morphology variation of Brassica chimeras was only controlled by red cabbage and was reproducible and directional in progenies [30].…”
Section: Donor Dominant Metabolite Analysis In Occmentioning
confidence: 99%
“…For instance, researchers have found that some conserved miRNAs were differentially expressed in graft chimera (Brassica juncea + B. oleracea) progeny rTTT (sexual self-crossing of the chimera) and donor plant TTT (B. juncea),, which may contribute to the changes in the expression of their target genes [30]. Furthermore, in graft chimeras of Brassica juncea and B. oleracea, sequencing analysis revealed that DNA methylation affects flowering time-and gibberellin response-related gene expression and may lead to phenotypic variations in progenies [46].…”
Section: Speculation Of Genetic Laws In the Metabolites Of Chimerasmentioning
confidence: 99%